Accuracy of colorectal cancer ICD-9-CM codes in Italian administrative healthcare databases: a cross-sectional diagnostic study. Issue 7 (5th July 2018) - Cozzolino, Francesco; Bidoli, Ettore; Abraha, Iosief; Fusco, Mario; Giovannini, Gianni; Casucci, Paola; Orso, Massimiliano; Granata, Annalisa; De Giorgi, Marcello; Collarile, Paolo; Ciullo, Valerio; Vitale, Maria Francesca; et al.
Abstract : Objectives To assess the accuracy of International Classification of Diseases, Ninth Revision – Clinical Modification (ICD-9-CM) codes in identifying subjects with colorectal cancer. Design: A diagnostic accuracy study comparing ICD-9-CM codes (index test) for colorectal cancers with medical chart (as a reference standard). Case ascertainment based on neoplastic lesion(s) within the colon/rectum and histological documentation from a primary or metastatic site positive for colorectal cancer. Setting: Administrative databases from the Umbria region, Azienda Sanitaria Locale (ASL) Napoli 3 Sud (NA) region and Friuli Venezia Giulia (FVG) region. Participants: We randomly selected 130 incident patients from each hospital discharge database, admitted between 2012 and 2014, having colorectal cancer ICD-9 codes located in primary position, and 94 non-cases, that is, patients having a diagnosis of cancer (ICD-9 140–239) other than colorectal cancer in primary position. Outcome measures: Sensitivity, specificity and predictive values for 153.x code (colon cancer) and for 154.x code (rectal cancer). Results: The positive predictive value (PPV) for colon cancer diagnoses was 80% for Umbria (95% CI 73% to 87%), 81% for NA (95% CI 73% to 88%) and 80% for FVG (95% CI 72% to 87%). The sensitivity ranged from 98% to 99%, while the specificity ranged from 78% to 80% in the three units. For rectal cancer, the PPV was 84% for Umbria (95% CI 77% to 90%), 80% for NA (95% CI 72% to 87%) and 81% for FVG (95% CI 73% to 87%). The sensitivities ranged from 98% to 100%, while the specificity estimates from 79% to 82%. Conclusions: Administrative databases in Italy can be a valuable tool for cancer surveillance as well as monitoring geographical and temporal variation of cancer practice.